Uji Antagonis Bacillus sp. dan Pseudomonas berfluorescens dari PGPR Akar Bambu Dalam Menekan Penyakit Layu Bakteri Ralstonia solanacearum Pada Tomat - Imam Sohibi; Yusriadi Marsuni; Elly Liestiany (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Bacterial wilt disease caused by Ralstonia solanacearum on tomato plants can reduce the quantity and quality, so it is necessary to control this disease. One of the controls that can be used is control using antagonistic agents. Bacteria Bacillus sp. and Pseudomanas fluorescens is an antagonist agent contained in PGPR which has the ability to suppress disease growth, increase plant root uptake of several nutrients and increase plant growth. This study aims to determine the effect of Bacillus sp. and P. fluorescens from bamboo roots in suppressing bacterial wilt disease of R. solanacearus in tomatoes. Using a Completely Randomized Design Method (CRD) consisting of 3 treatments, each treatment consisted of 6 replications so that 18 experimental units were obtained in vivo. Observations were made by measuring plant height, number of fruit, fruit weight and intensity of disease attack. The results obtained in this study indicate that the administration of Bacillus sp. and P. fluorescens were able to control bacterial wilt disease caused by Ralstonia solanacearum bacteria in tomato plants.